Socioeconomic impact of the war on the hydropower sector of Ukraine - Matus, Svitlana; Wasilewski, Mirosław; Włodarczyk, Tomasz; Zabolotnyy, Serhiy (Turystyka i Rozwój Regionalny, 2024)
The invasion of Ukraine on February 24, 2022, caused significant military damage to the hydropower sector, critical for energy security and economic development. The article provided an overview of the Ukrainian hydropower sector and the war’s socioeconomic impact on it in 2022-2024. Based on open source data, the research focused on large and small hydropower facilities, examining their roles in electricity generation, stability of the unified energy system of Ukraine, and water supply. The authors’ findings offer insights into the extent of damage for policymakers, scientists, and sector experts.